Association between arbuscular mycorrhizal fungi and Pratylenchus brachyurus in maize crop - Brito,Olivia Diulen Costa (Instituto de Investigaciones Agropecuarias, INIA, 2018)
ABSTRACT Maize (Zea mays L.) is one crop of major relevance in Brazil; however, nematodes are limiting factors in maize growth and productivity due to the difficulty to control them. Studies point out that arbuscular mycorrhizal fungi (AMF) increase plant tolerance to nematodes. Thus, the aim of this study was to assess the association between AMFs and Pratylenchus brachyurus in maize growth. Six AMF species (Rhizophagus clarus, Claroideoglomus etunicatum, Gigaspora rosea, G. margarita, Scutellospora calospora, S. heterogama), as well as a control treatment free of mycorrhizae, were assessed under two different nematode inoculum conditions (presence and absence). Plants were collected and analyzed 60 d after inoculation. The nematode population was higher in the treatments inoculated with AMFs. On the other hand, just the plants inoculated with R. clarus did not present improved development in comparison to the control. Nematodes increased AMF spore density, but despite the fact that AMFs have presented different root colonization capacity (ranging from 2.3% to 95.0%), such capacity was not affected by the nematodes